2001
DOI: 10.1021/bc015519e
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Modulation of Michael-Type Reactivity of Thiols through the Use of Charged Amino Acids

Abstract: A quantitative structure-reactivity relationship for the Michael-type addition of thiols onto acrylates was determined. Several thiol-containing peptides were investigated by examining the correlation between the second-order rate constant of their addition onto PEG-diacrylate and the pK(a) of the thiols within a peptide. By introducing charged amino acids in close proximity to a cysteine, the pK(a) of the thiol was systematically modulated by electrostatic interactions. Positive charges from the amino acid ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
361
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(380 citation statements)
references
References 27 publications
18
361
0
1
Order By: Relevance
“…Consequently, the protonated thiol form of cysteine may serve as the preferred nucleophile relative to the thiolate that is the predominant species occurring under basic conditions. This is in contrast to previous reports which indicated that in Michael-type reactions, thiolates (S Ϫ ) rather than thiols (SH) are the generally preferred nucleophiles° [23][24][25].°However,°our°observed°K3°reac-tion kinetics are consistent with an earlier study showing that protonated cysteine thiols are reactive to Michael acceptors having an ␣,␤ unsaturated carbonyl system,°such°as°K3° [26].…”
Section: Discussionsupporting
confidence: 63%
“…Consequently, the protonated thiol form of cysteine may serve as the preferred nucleophile relative to the thiolate that is the predominant species occurring under basic conditions. This is in contrast to previous reports which indicated that in Michael-type reactions, thiolates (S Ϫ ) rather than thiols (SH) are the generally preferred nucleophiles° [23][24][25].°However,°our°observed°K3°reac-tion kinetics are consistent with an earlier study showing that protonated cysteine thiols are reactive to Michael acceptors having an ␣,␤ unsaturated carbonyl system,°such°as°K3° [26].…”
Section: Discussionsupporting
confidence: 63%
“…Given that PEG is highly hydrophilic and generally nonadhesive to proteins or cells, it has found widespread use as a drug carrier [14], and many PEG hydrogels have been produced from aqueous solutions containing linear or branched PEG macromolecules via chemical crosslinking [15][16][17][18]. In addition to hydrogels formed via radical crosslinking reactions, PEG hydrogels have been formed, for example, via Michael-type addition reactions upon mixing with thiol-bearing compounds [19,20] or via the reaction between amino-terminated poly (ethylene glycol) and the herbal iridoid glycoside genipin [21]. In some cases, cell adhesive peptide domains or biodegradable sequences have been introduced into PEG hydrogels to endow them with biological signaling functions [22], including the capacity for growth factor delivery.…”
Section: Introductionmentioning
confidence: 99%
“…According to the work of Hubbell and Tirelli, 19 Michael-type addition of thiols to unsaturated esters offers an interesting route for networking functionalized polymer chains without using a photoreticulation process. In this context, we have studied the kinetics of the addition of thiol end-capped PVA chains to grafted PVA-MA.…”
Section: Resultsmentioning
confidence: 99%
“…19 This effect can be explained by the limited diffusivity of the macromolecular chains involved in the addition reaction. However, a similar rate constant for the addition of , -methylethylcysteine to acrylonitrile, i.e., 0.26 M -1 min -1 has been reported in the literature.…”
Section: Resultsmentioning
confidence: 99%